2019
DOI: 10.3390/ijerph16203985
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk and Restoration Measures Relating to Heavy Metal Pollution in Industrial and Mining Wastelands

Abstract: In this study, we applied an integrated approach to an ecological risk evaluation of heavy metal pollution in industrial and mining wastelands in Yangxin County, China. A total of 72 sampling sites were designated in the study area. The results show that the potential ecological risk levels of Hg and Cd are higher, and the coefficient of variation of mercury levels is large. Cr, Cu, Zn, Pb, Ni, and As are all at low potential ecological risk. The land types with relatively high ecological risks are alum and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…In [14]. Especially, Cheng's study [43] in the southern part of Hubei province is completely consistent with the results of the current study. Cd and Hg have high potential ecological risks and large coefficients of change, whereas Pb, Cr, Cu, Ni, Zn, and As have low potential ecological risks.…”
Section: Potential Ecological Assessmentsupporting
confidence: 90%
See 1 more Smart Citation
“…In [14]. Especially, Cheng's study [43] in the southern part of Hubei province is completely consistent with the results of the current study. Cd and Hg have high potential ecological risks and large coefficients of change, whereas Pb, Cr, Cu, Ni, Zn, and As have low potential ecological risks.…”
Section: Potential Ecological Assessmentsupporting
confidence: 90%
“…Meanwhile, the study regions have abundant mine resources, which are also a reason for the difference in concentration distribution of similar industries. Cheng et al indicated that the risk caused by Hg is high in alum mine soil, whereas the risk caused by Cd is relatively high in coal mine soil [43]. This finding shows that heavy metal pollution will occur in the mining process of coal and metal mines, and it is closely related to ore composition.…”
Section: Pollution Concentration Of Heavy Metals In Soilmentioning
confidence: 99%
“…The multi-solution and multiobjective nature of abandoned industrial and mining land redevelopment has been verified in several studies. The challenge of determining the final type of redevelopment, has undergone several stages of theoretical guidance from academics and practitioners: from the priorities of agricultural land that simply pursues increased production, construction land that pursues economic use value, or ecological land that pursues higher ecological service value, to the maximization of the combined benefits of nature, economy, and ecology [44,45]. The index system constructed in this study was first assessed by each single index, then integrated and calculated to determine the priority.…”
Section: Prioritization Of Redevelopment Of Abandoned Industrial and Mining Sitesmentioning
confidence: 99%
“…Coal mining operations exert a substantial impact on the environment, mainly manifested as surface subsidence, cracks, and waste accumulation (Li, 2006). Open‐pit coal mining removes the overburden and exposes the bare rock surface, which leads to the destruction and degradation of vegetation (Qian et al, 2014), heavy metals pollution (Cheng et al, 2019; Liu et al, 2017), and a marked decline in biodiversity and carbon pools (Ahirwal & Maiti, 2018). Additionally, the coal gangue generated by mining occupies substantial land area (Sun et al, 2018; Yang et al, 2014), and can cause the occurrence of soil erosion and geological disasters, including mudslides, landslides, slope instability, and rocky desertification (Wang et al, 2020; Zhang, Fu, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Coal mining operations exert a substantial impact on the environment, mainly manifested as surface subsidence, cracks, and waste accumulation (Li, 2006). Open-pit coal mining removes the overburden and exposes the bare rock surface, which leads to the destruction and degradation of vegetation (Qian et al, 2014), heavy metals pollution (Cheng et al, 2019;Liu et al, 2017), and a marked decline in biodiversity and carbon pools (Ahirwal & Maiti, 2018).…”
mentioning
confidence: 99%